An Instrument Development to Measure the Creative Habits of Mind for Prospective Elementary School Teachers - Maulidah, Neni; Sapriya, Sapriya; Supriatna, Nana (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to produce an instrument for measuring the creative habits of mind for prospective elementary school teachers in relation to developing creative teaching and learning ideas. This study is development research using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation. The study was conducted by involving one expert validator and one practitioner validator. At the implementation stage, trials were carried out on a number of 15 prospective elementary school teacher students. Data collection was carried out using a questionnaire and analyzed using qualitative and quantitative data analysis. Â The results of the instrument validations for measuring creative habits of mind show that creativity development and creative pedagogy development experts consider the instrument to be well qualified and suitable for measuring the creative habits of mind for prospective elementary school teacher students. The average test results in small groups of both lecturers and students show that the resulting instruments are in good qualifications. The end result of this development research is an instrument for measuring the creative habits of mind for prospective elementary school students who are Â well-qualified, appropriate, and ready to use.